Trauma exposure and PTSD among men entering jail: A comparative study with the general population. (January 2022) - Fovet, Thomas; Wathelet, Marielle; Amad, Ali; Horn, Mathilde; Belet, Bettina; Benradia, Imane; Roelandt, Jean-Luc; Thomas, Pierre; Vaiva, Guillaume; D'Hondt, Fabien
Abstract: Research has consistently shown high levels of post-traumatic stress disorder (PTSD) in correctional settings. We aimed to compare the prevalences of trauma exposure, subthreshold PTSD, and full PTSD in incarcerated people with those observed in the general population. We used the Mini-International Neuropsychiatric Interview to screen for psychiatric disorders among men upon admission to jail (N = 630) and non-incarcerated men living in the same geographic area (the northern district of France; N = 5793). We utilized a multinomial regression model to assess the association between admission to jail and the prevalences of trauma exposure, subthreshold PTSD, and full PTSD. We employed logistic regression models to verify the interaction between admission to jail and PTSD status on the presence of psychiatric comorbidities. Full PTSD was overrepresented among men in jail after adjustment for all covariates (OR [95% CI] = 3.49 [1.55–7.85], p = 0.002). The association between PTSD status and the presence of at least one psychiatric comorbidity was also more important upon admission to jail than in the general population. Admission to jail was not associated with a higher prevalence of trauma exposure (OR [95% CI] = 1.12 [0.85–1.46], p = 0.419) or subthreshold PTSD (OR [95% CI] = 1.17 [0.81–1.68], p = 0.413). These results suggest higher prevalence rates of full PTSD and psychiatric comorbidities associated with PTSD symptoms in incarcerated people than in the general population. The provision of trauma-focused interventions tailored to these clinical specificities should be considered for the jail population. Highlights: PTSD is over-represented in men recently admitted to jail compared to the general population. People with a history of incarceration but also first-time entrants to jail show a higher rate of full PTSD. Psychiatric comorbidities associated with PTSD symptoms are more frequent in jailed people than in the general population.